IMPACT OF STEVIA (STEVIA REBAUDIANA BERT.) POLYPLODIZATION ON LEAF YIELD AND ATTRIBUTES - SHREERAM NARASIMHA HEGDE; CHAVAN NARENDRASING RAMESHSING; M. VASUNDHARA (The Bioscan, 2015)
A field experiment was carried out at Department of Horticulture, University of Agricultural Sciences, Bangalore (Karnataka) during 2013-14 to evaluate stevia (Stevia rebaudiana Bert.) polyploids for higher biomass and to work out the cost of cultivation. The experiment was laid out by adapting Randomized Complete Block Design with ten treatments and three replications. The treatment included nine induced polyploids of stevia with varied ploidy levels and one untreated diploid. Significant differences were observed with respect to yielding ability of the plant. At harvest the yield parameters viz.,leaf thickness (0.57 mm), leaf area (15.00 cm2), fresh weight of leaves (126.63 g/ plant), dry weight of leaves (32.90 g/ plant) were maximum in mixaploid, with 93.99% increase in yield compare to normal diploids. From the present investigation it can be conclude that, yield performance of all induced polyploids were better compare to diploid. Among the polyploids mixaploid shown best results with respect to yielding ability.